Modernization of Da'wah Methods in Fostering Interest Among Young Generation (Case Study QS. Al-Ahzab Verse 46) - Saputra, Wahyu; Akbar, Ali; Burhanuddin, Burhanuddin (INJIES: Journal of Islamic Education Studies, 2024)
This article discusses the relevance of verse 46 of Surah Al-Ahzab in the context of modern da'wah. The verse implies three important elements in da'wah: the call, Allah's permission, and the guiding light. Considering these principles, da'wah methods can be modernized to reach the younger generation. The research method used in this study is a qualitative approach by utilizing in-depth interviews and literature studies to explore the relevance of QS Al-Ahzab Verse 46 in the context of modern da'wah. Modern approaches include leveraging social media, creating digital content, mobile applications, social activities, and education. Furthermore, the article also discusses the differences between classical and modern da'wah methods, as well as their respective advantages and characteristics. By combining tradition with technology, da'wah can effectively reach more people in the modern era. However, modern methods such as social media, websites, podcasts, mobile apps, and online seminars or webinars, provide greater flexibility and reach, as well as allow for direct interaction and easier access to information. This integration between classical and modern methods ensures effective, educational, and relevant da'wah to the needs of the times.